Born a Culturally Responsive Educator: A Conversation With Dr. Cathy Kea. (November 2022) - Jones, Vita L.; Higgins, Kyle; Boone, Randall
Dr. Cathy Kea is a professor of special education in the Department of Educator Preparation at North Carolina A&T State University. Dr. Kea's research interests focus on the intersection among general education, special education, and multicultural education, which she has labeled "a trilogy to be transformed." Her current research focuses on preparing preservice teachers to design and deliver culturally responsive instruction in urban classrooms as well as providing methods, materials, and philosophy to educator preparation programs (e.g., via syllabi, lesson plans, lectures).